Alcohol consumption, depression, overweight and cortisol levels as determining factors for NR3C1 gene methylation - Júlia de Assis Pinheiro; Flávia Vitorino Freitas; Aline Ribeiro Borçoi; Suzanny Oliveira Mendes; Catarine Lima Conti; Juliana Krüger Arpini; Tamires dos Santos Vieira; Rafael Assis de Souza; Dirceu Pereira dos Santos; Wagner Miranda Barbosa; Anderson Barros Archanjo; Mayara Mota de Oliveira; et al. (Scientific Reports, 2021)
Abstract The NR3C1 glucocorticoid receptor (GR) gene is a component of the stress response system, which can be regulated by epigenetic mechanisms. NR3C1 methylation has been associated with trauma and mental issues, including depression, post-traumatic stress, anxiety, and personality disorders. Previous studies have reported that stressful events are involved in NR3C1 gene methylation, suggesting that its regulation under environmental effects is complex. The present study aimed to analyze associations involving stressors such as socioeconomic status, health conditions, and lifestyle in relation to NR3C1 methylation in adults. This study included 386 individual users of the Brazilian Public Unified Health System (SUS), and evaluated socioeconomic and health conditions, body mass index, cortisol levels, and lifestyle. Data were correlated with NR3C1 methylation, determined using DNA pyrosequencing. The results showed that alcohol consumption, overweight, and high cortisol levels were related to NR3C1 demethylation, while depression was related to its methylation. Habits, lifestyle, and health status may influence NR3C1 gene regulation via methylation, revealing the complexity of environmental impacts on NR3C1 methylation.